Electrochemical analysis of butylated hydroxytoluene - Rosyiidah, Nur Anisa; Pirim Setiarso (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Electrochemical analysis has carried out butylated hydroxytoluene (BHT) measurements. Cyclic voltammetry is used in this research as a qualitative-quantitative analysis of oxidation and reduction reaction processes, adsorption processes on electrode surfaces, and chemical electron transfer mechanisms. This research aims to determine the optimum deposition time and scan rate in cyclic voltammetry, the BHT standard equation, the limit of detection, and the recovery percentage. In this research, a deposition time of 25 seconds produces the highest current response of 3.89672 x 10-4 Ampere. The scan rate is 150 mV/second, producing the highest and optimum current response of 4.24561 x 10-4 Ampere. BHT standard equation y = (4.92784 x 10-6) x + (1.25207 x 10-4) is obtained with R2 = 0.99933. The limit of detection value is 2.69683 ppm, and the recovery percentage is 101.314%. Therefore, this cyclic voltammetry method is suitable for analyzing BHT because it has high sensitivity.